The Dolichopodainae and Troglophilinae cave crickets of Turkey: an update of taxonomy and geographic distribution (Orthoptera, Rhaphidophoridae) - Taylan, Mehmet S.; Russo, Claudio Di; Cobolli, Marina; Cobolli, Marina (Zootaxa, 2011)
In this note we report a new series of data on Dolichopodainae and Troglophilinae cave crickets of Turkey, after an extensive survey conducted between the years 2006 and 2010 in the main Anatolian cave systems. These new data, including the identifications of some undescribed taxa, are discussed in the framework of climate regions, vegetation and karst distribution of Turkey, contributing to the study of diversity and geographical distribution of Rhaphidophoridae cave crickets from Turkey.